Potential Of Aqueous Extracts From Weeds And Food Crops In Oil Palm Plantations As Bioherbicides - Susi Handayani; Andreani Kinata; Edi Susilo (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to test water extracts derived from weeds and plants in oil palm plantations on the germination of test plants. The extract was prepared from June to July 2024 in Arga Makmur, North Bengkulu Regency, and the bioassay test was conducted from July to August 2024 in Pematang Gubernur, Muara Bangkahulu, Bengkulu City. Methodology: The study used a single-factor, completely randomized design. Twenty-one treatments were applied, namely, the source of extracts from broadleaf weeds, grass weeds, and teki weeds of 5 types each, as well as the control. The experimental unit was a Petri dish, and the experiment was repeated four times. The petri dish bioassay method was applied in this experiment. Each petri dish was given 10 mL of water extract, and 25 mung bean seeds of the Vima 2 variety were planted and incubated for three days. Results: The results showed that water extracts derived from weeds and plants in oil palm plantations significantly affected almost all variables. Findings: Water extracts that inhibit the germination of the highest test plants come from broadleaf weeds, namely Ageratum conyzoides, Chromolaena odorata, Stenochlaena palustris, Wedelia trilobata, and Amaranthus sp. Food crop groups are Oryza sativa, Manihot esculenta, Ipomoea batatas, and Vigna radiata. Grass weeds were Leersia hexandra and Eleusine indica, and no weeds were in the weed class. Novelty: This study provides insight into the potential of allelopathy sourced from weeds and food crops. Originality: This study offers a detailed analysis of the bioherbicidal effects of weed and food crop extracts on seed germination or test plants. Conclusion: Aqueous extracts of broadleaf weeds dominated the inhibition of seed germination and have great potential as bioherbicides. Document type: empirical research article. Keywords: weeds; oil palm plantations; extract sources; food crops; bioherbicides